Analisis Faktor Kecemasan Pasien Kanker Serviks saat Kemoterapi - Siti Mulidah; Sri Hidayati; Ahmad Baequny (Prodi Keperawatan Purwokerto, 2021)
Background: Chemotherapy have some side effects for physic or psychology of client, one of that is anxiety. Anxiety on cervical cancer client that follow this chemotherapy may make client reschedule their chemotherapy or they will stop the chemotherapy.Method: The purpose of this study is to determine the factors that affect the anxiety of cervical cancer patients in following chemotherapy. This research used cross sectional study. The sample of this research are cervical cancer patients who followed chemotherapy as many as 32 persons with insidental sampling method. Data were analyzed using Chi-Square Test with significance level of 0.05 and regression test with significance level of 0,25.Result: confirmed that 57.1% of respondents skilled slight tension. Then, the effects additionally located that there's a considerable courting among maturity, own circle of relatives assist, social assist with cervical most cancers tension in following chemotherapy.Conclusion: the dominant factor that affects the anxiety of cervical cancer patients in following chemotherapy program is maturity. supply them know-how approximately chemotherapy and the impact and supply them greater informative assist and emotional assist Keywords: Anxiety, Cervical Cancer, Chemotherapy, Maturity, Family Support, Social Support